The associations between orthostatic blood pressure changes and extracellular volume in hemodialysis patients. Issue 1 (16th August 2021) - Jeon‐Slaughter, Haekyung; Gregg, Lucile Parker; Concepcion, Michael; Lederer, Swati; Penfield, Jeffrey; Van Buren, Peter Noel
Abstract: Introduction: Extracellular volume (ECV) predicts mortality in hemodialysis patients, but it is difficult to assess clinically. Peridialytic blood pressure (BP) measurements can help ECV assessment. Orthostatic BP is routinely measured clinically, but its association with ECV is unknown. Methods: In a cohort of hypertensive hemodialysis patients, we measured posthemodialysis ECV/weight with bioimpedance spectroscopy and analyzed its association with post‐HD orthostatic BP measurements obtained during routine care. Using linear and logistic regression, the primary outcomes were orthostatic BP change and orthostatic hypotension (OH) defined by systolic BP decrease of at least 20 mmHg or diastolic decrease of at least 10 mmHg. Model 1 controlled for sex, age, and diabetes. Model 2 additionally controlled for ultrafiltration rate and antihypertensive medications. We conducted sensitivity analysis using OH definition of systolic BP decrease of at least 30 mmHg. Findings: Among 57 participants, mean orthostatic systolic BP change was −7.30 (20) mmHg and mean ECV/weight was 0.24 (0.04) L/kg. Post‐HD ECV/weight was not associated with orthostatic systolic BP change ( β = 8.2, p = 0.6). There were 16 participants with and 41 participants without OH. The ECV/weight did not differ between these groups (0.22 [0.04] vs. 0.24 [0.05] L/Kg, p = 0.09) and did not predict OH in logistic regression (OR 11, 4.04; 95% CI 0.2–671, 0.03–0.530 in the two models.) In a sensitivity analysis, ECV/weight was lower in the OH group (0.22 [0.03] vs. 0.25 [0.04] L/kg, p = 0.005), but this was accompanied by differences in sex and diabetes. Using logistic regression, there was no independent association between ECV/weight with OH. Discussion: Orthostatic systolic BP change after HD completion is not a reliable indicator of posthemodialysis ECV. When considering other factors associated with orthostatic BP, ECV/weight is not independently associated with OH. Although transient postdialytic differences in intravascular volume may be associated with OH, posthemodialysis OH does not necessarily indicate ECV depletion.